Short‐Range Atomic Topology of Ab Initio Generated Amorphous PdSi Alloys. Issue 4 (8th February 2023) - Rodríguez, Isaías; Valladares, Renela M.; Valladares, Alexander; Hinojosa‐Romero, David; Valladares, Ariel A.
Abstract: Since the pioneering efforts of Duwez and co‐workers in 1965, when a solid amorphous phase of palladium‐silicon (a‐PdSi) was obtained in the vicinity of the eutectic concentration, much work has been done. However, some points related to the atomic structures remain to be systematized. In this work, 8 amorphous Pd100‐c Sic alloys ( c = 2.5, 5, 10, 13.34, 15, 17.5, 20, and 22 at%) are generated by molecular dynamics ab initio simulations; the short‐range structure is analyzed using several correlation functions, like Pair Distribution Functions, reduced Pair Distribution Functions, Plane Angle Distribution Functions. Other related properties, like nearest‐neighbors and some Frank–Kasper polyhedra are reported. The generated samples correctly reproduce the scarce experimental pair correlation functions that are reported in the literature. An unexpected outcome is the appearance of structural changes in the neighborhood of Pd86.66 Si13.34 . Abstract : Structural short‐range features of the PdSi amorphous system are reported for eight different concentrations. The amorphous structures, obtained by a first‐principles molecular dynamics approach, are described by several correlation functions. The short‐range order is analyzed using Frank–Kasper polyhedra and coordination numbers. Local atomic arrangement may be important to explain the magnetism previously reported.